E3 Ubiquitin Ligase CHIP Inhibits the Interaction between Hsp90β and MAST1 to Repress Radiation Resistance in Non-Small-Cell Lung Cancer Stem Cells - Bo Tan; Jingwei Zhang; Wen Wang; Haibo Ma; Yuanyuan Yang (Hindawi Limited, 2022)
The radiation resistance of cancer stem cells poses a critical obstacle for management of non-small-cell lung cancer (NSCLC). It is interesting to note that E3 ubiquitin ligase CHIP is involved in radiation resistance and stemness phenotypes in NSCLC, while the downstream mechanisms remain elusive. Therefore, this study is aimed at exploring the possible molecular mechanism of E3 ubiquitin ligase CHIP in radiation resistance of NSCLC stem cells. Cancer and adjacent normal tissues of NSCLC patients were collected to determine expression of CHIP, Hsp90β, and MAST1. CD133+ cells were isolated from the NSCLC tissues and the lung cancer cell line A549 by flow cytometric sorting. Accordingly, downregulated CHIP and upregulated Hsp90β and MAST1 were observed in cancer tissues from NSCLC patients and in NSCLC stem cells. Sphere formation assay, colony formation assay, and flow cytometry were performed to examine self-renewal ability, survival, and apoptosis of NSCLC stem cells. An animal model of tumor xenograft was developed in nude mice to observe the tumorigenic ability and radiation resistance of NSCLC stem cells. CHIP overexpression was demonstrated to inhibit the NSCLC stem cell properties and radiation resistance in vitro and in vivo. Mechanistically, CHIP promoted MAST1 ubiquitination by blocking Hsp90β interaction with MAST1, thus inhibiting MAST1 protein stability. Furthermore, CHIP-mediated downregulation of MAST1 protein stability inhibited the NSCLC stem cell properties and radiation resistance. Collectively, CHIP promotes the ubiquitination of MAST1 by blocking the interaction of Hsp90β with MAST1, leading to decreased MAST1 protein stability, which suppressed NSCLC stem cell properties and radiation resistance.